Multiple solutions for mixed boundary value problems with ϕ-Laplacian operators - Dallos Santos, Dionicio Pastor (2020)
Using Leray-Schauder degree theory and the method of upper andlower solutions we establish existence and multiplicity of solutions for problemsof the form(ϕ(u0))0 = f(t, u, u0)u(0) = u(T) = u0(0),where ϕ is an increasing homeomorphism such that ϕ(0) = 0, and f is acontinuous function.